Effect of Solvent on the Growth of Various Proportion of Organic Mixed Crystal - MADHURAMBAL, G.; MARIAPPAN, M. (Asian Journal of Chemistry, 2010)
The induction period of various proportion of urea-thiourea mixed crystal in water has been measured experimentally by the visual observation method. The induction period, which is inversely proportional to the nucleation rate, has been used to estimate the interfacial tension between the urea-thiourea mixed crystal and water, hence the nucleation parameters like critical radius (r*), number of molecules in the radius (r*) and Gibbs free energy change for the formation of a critical nucleus (ΔG*) have been calculated.